ADAPTIVE CONTROL OF THOUGHT OUTPUT MODEL: ENGLISH GRAMMAR TEACHING METHOD FOR NON-NATIVE STUDENT A CLASSROOM RESEACH STUDY AT SMA 4 PRAYA - Lalu Dwi Satria Ardiansyah (Jurnal Ilmiah Mandala Education (JIME), 2017)
This study was aimed at improving the teaching ofgrammar of the eleventgradenon-native students at SMA 4 Prayaby using Adaptive Control of Thought Output Model. This research was action research which consisted of two cycles with threemeetings in each cycle.  The subjects of this research were the researcher, the students, the English teacher, and the collaborators. The data collection techniques were observations, interviews, and tests. The data were in the form of qualitative data and quantitative data. The qualitative data were obtained from the field notes and interview transcripts. These  data  were analyzed  using  five  steps i.e. assembling  the  data,  coding  the data,  comparing  the  data,  building  interpretations,  and  reporting  the  outcomes. Meanwhile, the quantitative data were obtained from the pre-test and the post-test scores.  These data were analyzed by comparing the mean scores of the pre-test and the post-test. The results of the research show that the use of the Adaptive Control of Thought Output Model in combination with applying various media and activities, such as pictures and games, could improve the teaching of grammar. Based on the qualitative data, the teaching activities become more well-planned and structured. From  the  group  work  activities,  the  students  could  build  their  cooperation  and improve  their  participation.  The  uses  of  games  and  pictures  could  facilitate  the students  to  understand  the  texts  easily. Based on the quantitative data, the students’ grammar comprehension scores increased. The students’ mean score increased from 65.54 to 73.97.  The  improvement  on  the  students’  mean  scores  showed  that  the improvement  of  the  teaching  of  grammar gave  impacts  to  the  students’ achievement. From the data above, it can be concluded that the use of the Adaptive Control of Thought Output Model can improve the teaching of grammar for non native students.